Critical review of the Abe administration : politics of conservatism and realism - Nakakita, Koji (Oxon : Routledge, 2024)
"The second Abe administration, which lasted for seven years and eight months, turned out to be the longest administration in Japan s constitutional history. What factors contributed to its remarkable longevity? What accomplishments and enduring legacies did this administration achieve during its tenure? Originally published in Bungeishunju in Japanese, this book examines policies pursued by the administration and its governance based on over 50 investigative interviews with key figures in the administration, including former Prime Minister Shinzo Abe. The contributors cover nine major policies, including economic policy, diplomacy and security, work style reform, trade liberalization, and historical issues, and explore why a specific policy was chosen at that time, who made that decision, and on what grounds. Reviewing such decision-making processes sheds light on the issue of governance. Consequently, this book also analyses the administration s distinctive style of governance, such as strong leadership from the Prime Minister s Office, ability to navigate party politics, and overwhelming victories in national elections. An essential for scholars and students in the fields of public administration, public policy, Japanese studies, and Asian Studies."--
Keywords: Abe, Shinzō, -- 1954-2022.; National security--Japan--History--21st century; Japan--Economic conditions--21st century